2003
DOI: 10.1038/sj.bjp.0705507
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of 5‐HT1A receptor‐mediated gastric relaxation in conscious dogs

Abstract: 1 Accumulating data have been published emphasizing the important role of 5-hydroxytryptamine (5-HT) receptors in proximal stomach relaxation. However, a proper in vivo characterization of 5-HT receptors mediating gastric relaxation is still missing. In the current study, we focus on the in vivo characterization of 5-HT 1A receptors mediating relaxation of the proximal stomach in conscious dogs. 2 Beagle dogs were equipped with a gastric fistula. In the conscious state, volume changes within an intragastric ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Although R137696 has a higher affinity for 5‐HT 1A receptors compared to 5‐HT 1B or 5‐HT 1D receptors, this does not exclude the possibility that it may relax the stomach by the same mechanism as sumatriptan. On the other hand, R137696 induced gastric relaxation could be mediated by a vagal pathway without the involvement of nitrergic neurons, as recently shown in dogs for the 5‐HT 1A agonist flesinoxan 19 . Finally, R137696 could act by central mechanisms.…”
Section: Discussionmentioning
confidence: 64%
“…Although R137696 has a higher affinity for 5‐HT 1A receptors compared to 5‐HT 1B or 5‐HT 1D receptors, this does not exclude the possibility that it may relax the stomach by the same mechanism as sumatriptan. On the other hand, R137696 induced gastric relaxation could be mediated by a vagal pathway without the involvement of nitrergic neurons, as recently shown in dogs for the 5‐HT 1A agonist flesinoxan 19 . Finally, R137696 could act by central mechanisms.…”
Section: Discussionmentioning
confidence: 64%
“…Our present findings indicate that also 5‐HT release is part of this balance. Possible receptors that could decrease gastric tone are 5‐HT 1 , 5‐HT 4 and 5‐HT 7 receptors 4, 26–28 . It has been shown that the 5‐HT 4 receptor antagonist R216073 did not affect basal gastric volumes, 10 which indicates that 5‐HT 1 and/or 5‐HT 7 receptors could be more likely candidates.…”
Section: Discussionmentioning
confidence: 99%
“…The receptor through which 5‐HT acts in the control of the accommodation reflex therefore remains to be identified. Experiments in dogs have characterized 5‐HT 1 and 5‐HT 7 receptors that might mediate gastric relaxation 23,24 although human studies addressing this hypothesis are lacking at present.…”
Section: Discussionmentioning
confidence: 99%